2022
DOI: 10.1111/rda.14220
|View full text |Cite
|
Sign up to set email alerts
|

The effect of priming and duration of oestradiol benzoate treatment before progesterone administration on embryo development and survival in anestrous recipient mares

Abstract: Embryo transfer (ET) is a common practice in equine-assisted reproduction programs. Mares are seasonal polyoestrous long day breeders and, the majority of them, undergo a period of winter anestrus (Aurich, 2011). Therefore, the use of hormonal protocols in seasonal anestrous mares is a crucial tool to increase the efficiency of ET clinical programs since it allows the possibility of transferring embryos outside the breeding season.Although progesterone alone can be used to prepare anestrous recipient mares to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…Furthermore, 24 h after the transfer of six embryos into an apparently optimal endometrial environment of a properly synchronized recipient mare, one embryo was already destroyed. This confirms the observation of a previous study in which a timing of 48 h after transfer was likely to be too long to recover embryos which did not resist a suboptimal environment [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, 24 h after the transfer of six embryos into an apparently optimal endometrial environment of a properly synchronized recipient mare, one embryo was already destroyed. This confirms the observation of a previous study in which a timing of 48 h after transfer was likely to be too long to recover embryos which did not resist a suboptimal environment [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…In fact, only capsule fragments (sign of a destroyed embryo) were found in 3 of 11 reinserted embryos, and even in one of 6 embryos transferred into an apparently optimal endometrial environment of a properly synchronized recipient mare, by only 24 h of transfer. This confirms the observation of a previous study in which a timing of 48 h after transfer was likely to be too long to recover embryos which did not resist a suboptimal environment [32].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, it is unknown too, whether these three embryos were able to develop normally because the endometrial environment was optimal or because these embryos were more resistant to a hostile environment. In this regard, it has been shown that even though most embryos require an endometrial environment that has been primed with oestrogens, around 40 percent of them can survive in recipient mares which had been treated with exogenous progesterone only [32,33], which are assumed to have a suboptimal endometrial environment [34].…”
Section: Discussionmentioning
confidence: 99%